The effect of technological innovation capabilities on corporate entrepreneurship and firm performance in the South African media and entertainment industry - Onwu, Ekenedilichukwu Gilbert (My University, 2016)
In order for developing countries like South Africa to not only compete in business at an international level, but to also establish a sustained competitive advantage in this increasingly integrated global business economy, a radical change in thinking is required. Technological innovation, knowledge and its application, which holistically explains an enterprise‟s technological innovation capability, are absolutely essential for modern firms looking to develop strategic and operational prowess on a global scale. Research in this field has largely highlighted the lack of technological innovation capabilities in developing regions around the world, and more recently the need for nations and firms to increasingly invest heavily in fostering technological innovation as a means for national economic growth. The same notion goes for the practice of corporate entrepreneurship, which has been internationally recognised as an integral aspect of firm survival, growth and relevance in all sectors and industries around the world. However, while several researchers agree that the relationship between technological innovation capabilities and corporate entrepreneurship is not clear, it is also vague as to the effect this relationship consequently has on organisational performance. Therefore, this research aims to delineate these relationships, specifically between technological innovation capabilities and corporate entrepreneurship, between technological innovation capabilities and organisational performance, between corporate entrepreneurship and organisational performance and through these constructs, shed some light on the investment capability of firms in these concepts in the context of the South African Media and Entertainment Industry. The research looks at the seven dimensions of technological innovation capabilities, the four dimensions of corporate entrepreneurship and a minor dimension on investment capability, all in relation to firm performance. This research employs both a regression and multi-correlation analysis to demonstrate the relationships between the two constructs and their individual relationships to firm performance.
A research report submitted to the faculty of Commerce, Law and Management, University of Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management in Entrepreneurship and New Venture Creation (MMENVC) Wits Business School, 2016
Keywords: Technological innovations--Economic aspects--South Africa.; Entrepreneurship; Organizational effectiveness